#TITLE_ALTERNATIVE# - SRI RAHAYU (NIM 10504025), RIA
Heterogeneous electron transfer rates of ascorbic acid oxidation on carbon paste electrode surface is slow as indicated by wide peak of its cyclic voltammogram. Therefore, it is not possible to analyze ascorbic acid with voltametric method directly using carbon paste electrode. Several modifications of carbon paste electrode have been done to accelerate the electron transfer. Carbon paste electrode modified with mediators immobilized in zeolite and wood powder have been made in this research for that purpose. Copper (II) ammonia complex, iron (III) phenanthroline complex, and methylene blue mediators show electrocatalytic effect in ascorbic acid analysis. However, iron (III) phenanthroline complex immobilized in zeolite shows the best performance of all mediators studied for amperometric analysis of ascorbic acid. Percent recovery of ascorbic acid is between 98.69-99.90 % in linear region of 10 μM-10 mM with detection limit of 1.74 μM. Analysis of a real sample using this electrode shows good results.